(x+y)2 - (x-y)2 = x2 + 2xy + y2 - x2 + 2xy - y2
= 4xy
(x+y)2 - (x-y)2 = x2 + 2xy + y2 - x2 + 2xy - y2
= 4xy
Rút gọn biểu thức
a,(x+y)2-(x-y)2
b,(x-y-z)2+(x+y+z)2
c,(x+y)2-2(x+y)(x-y)+(x-y)2
Cho x , y , z khác 0 và x + y = z =0 . Rút gọn biểu thức : \(A=\frac{x^2}{y^2+z^2-x^2}+\frac{y^2}{z^2+x^2-y^2}+\frac{z^2}{x^2+y^2-z^2}\)
Rút gọn biểu thức sau: (x + y + z)2 – 2(x + y + z)(x + y) + (x + y)2
Rút gọn biểu thức:
A= (x^2-y)(y+1)+x^2y^2-1/(x^2+y)(y+1)+x^2y^2+1
B= x^2(y-z)+y^2(z-x)+z^2(x-y)/x^2y-x^2z+y^2z-y^3
1) Rút gọn biểu thức sau :
a) (x+y)2+(x-y)2
b) 2(x-y)(x+y)+(x+y)2+(x-y)2
c)(x-y+z)2+(z-y)2+2(x-y+z)(y-z)
Rút gọn các phân thức sau: a) x^3+y^3+z^3-3xyz/(x-y)^2+(x-z)^2+(y-z)^2 b) (x^2-y^2)^3+(y^2-z^2)^3+(z^2-x^2)^3/(x-y)^3+(y-z)^3+(z-x)3
rút gọn biểu thức:
a) (x+y)2+(x-y)2
b) 2.(x-y).(x+y)+(x+y)2+(x-y)2
c) (x-y+z)2+(z-y)2+2.(x-y+z).(y-z)
a) (x+y+z)^2 - 2(x+y+z)(x+y)+(x+y)^2
b) (a+b)^3 - (a - b)^3 - 2b^3
c) (a + b)^2 - (a - b)^2
1. Rút gọn các biểu thức sau:
a) (a+b)^2-(a-b)^2
b) (a+b)^3-(a-b)^3-2b^3
c) (x+y+z)^2-2(x+y+z)(x+y)+(x+y)^2
Rút gọn biểu thức sau:
(x+y-z)2+(y-z)2+2(x-y+z)(z-y)